FACTOR ANALYSIS OF SUSTAINABILITY AND HALAL PRACTICES IN THE COFFEE INDUSTRY: A STUDY OF KENANGAN COFFEE CHAINS - Kuncorosidi Kuncorosidi; Rizky Sidik Firmansyah; Jojo Jojo (STIESA Press, 2025)
The global coffee supply primarily depends on smallholder farmers, with millions relying on coffee as their main income. Many of these farmers live below the poverty line, face challenges with mechanization due to hilly terrain, and lack access to stable contracts, credit, and knowledge for long-term investment. Climate change further threatens coffee production, potentially halving supply by 2050. Indonesia's leadership in the halal economy is driven by its large Muslim population, rising awareness of the halal lifestyle, and government support. In the Fourth Industrial Revolution, halal supply chain management now covers all stages, from raw materials to product distribution, ensuring comprehensive halal compliance. The method used in this research is a quantitative method with a descriptive research type. The population in this study includes all consumers of Kenangan Coffee. The sampling technique used is Non-Probability Sampling with a sample of 123 Kenangan Coffee consumers from all age groups who purchased coffee at Kenangan Coffee outlets throughout Indonesia. The results of the analysis indicate that sustainability practices are identified through four main factors, which include energy consumption efficiency, waste reduction, the use of sustainable materials, environmentally friendly products, commitment to the local community, financial sustainability, and gender equality in the workforce. Meanwhile, the analysis of halal practices resulted in three main factors, focusing on compliance with halal standards, cleanliness and quality in the production process, as well as consumer trust and satisfaction with halal products, including a willingness to pay more for certified halal products.